TANGGUNG JAWAB ILMUWAN DALAM PENEGAKAN HUKUM BERDASARKAN KEBENARAN DAN KEADILAN - Siringoringo, Poltak; Bello, Petrus (Fakultas Hukum Universitas Kristen Indonesia, 2025)
The responsibility of scientists is an ethical concept in which scientists are required to bear any consequences caused by the science itself, both from the theoretical side and the practical side, in the sense that scientists are required to answer and solve any problems caused by science or not caused by science itself. Scientific responsibility, in this case, is not a burden, but a characteristic of the dignity of science and the scientist itself. This paper will focus on the responsibility of scientists in enforcing the law based on truth and justice, by explaining and showing several important reasons why scientists need to be socially responsible in carrying out their scientific activities, explaining several forms of scientist responsibility based on professional standards of behavior and moral behavior as scientists, explaining the responsibility of scientists in the legal field in enforcing the law based on truth and justice, and explaining how to improve the attitude of scientist responsibility as part of improving their moral behavior as scientists.